Cochrane Database of Systematic Reviews 2006
DOI: 10.1002/14651858.cd004945.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Induction of labour for improving birth outcomes for women at or beyond term

Abstract: Background-As a pregnancy continues beyond term the risks of babies dying inside the womb or in the immediate newborn period increase. Whether a policy of labour induction at a predetermined gestational age can reduce this increased risk is the subject of this review. Objectives-To evaluate the benefits and harms of a policy of labour induction at term or postterm compared with awaiting spontaneous labour or later induction of labour. Search methods-We searched the Cochrane Pregnancy and Childbirth Group's Tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
286
9
54

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 300 publications
(370 citation statements)
references
References 78 publications
19
286
9
54
Order By: Relevance
“…We chose to compare women who underwent IOL at a specific GA to those who were expectantly managed. These findings are consistent with several large cohort studies and a meta-analysis in women without GDM that demonstrated no increase in the CD rate in women with who underwent IOL at term 25,26 .…”
Section: Commentsupporting
confidence: 92%
“…We chose to compare women who underwent IOL at a specific GA to those who were expectantly managed. These findings are consistent with several large cohort studies and a meta-analysis in women without GDM that demonstrated no increase in the CD rate in women with who underwent IOL at term 25,26 .…”
Section: Commentsupporting
confidence: 92%
“…85 However, birth before 39 weeks increases the risk of morbidity 86 and is associated with increased risk of long-term mortality. 87 Therefore, before 39 weeks, early delivery needs to balance any reduction in stillbirth risk against morbidity and long-term mortality of the offspring, and should only be considered in the presence of a substantial risk for maternal or neonatal complications.…”
Section: Antenatal Screening and Interventions To Prevent Stillbirth mentioning
confidence: 99%
“…Implementation research is needed on training, staffing, referral systems, procurement and maintenance of obstetric ultrasound for low-resource settings, as well as critical study of the clinical impact. Correct dating also affects management of post-term pregnancy, where induction of labour may avoid late intrauterine fetal death and labour-related perinatal death [20].…”
Section: Gestational Agementioning
confidence: 99%